Changes in serum lipid levels during pregnancy in women with gestational diabetes. A narrative review - Cibickova, Lubica; Schovanek, Jan; Karasek, David (Biomedical papers, 2021)
We review current knowledge on lipid metabolism changes during pregnancy with special focus on changes in gestational diabetes. In physiological pregnancy, total plasma cholesterol, triglyceride and HDL-cholesterol level rises, the atherogenic index (LDL-cholesterol / HDL-cholesterol remains unchanged. Compared with healthy women, women with GDM show more pronounced signs of mixed dyslipidaemia - increased levels of triglyceride, changes in cholesterol and lipoprotein concentrations with a shift towards greater small dense LDL subtractions, which is typical for insulin resistance states. Dyslipidaemia, particularly hypertriglyceridemia, is thought to be one of the key drivers of foetal macrosomia and that is why measurements of plasma lipids may be valuable in detecting the metabolic abnormality in GDM and in predicting foetal outcome. Dyslipidaemia in GDM is seen as proatherogenic and potentially harmful for the baby and therefore it should be monitored more carefully.
Keywords: plasma lipids; gestational dyslipidaemia; triglycerides; pregnancy; gestational diabetes; insulin resistance